Nereis taichungensis nom. nov., a replacement name for Nereis articulata Hsueh, 2020, a junior primary homonym to Nereis articulata Ehlers, 1887 - Hsueh, Pan-Wen (Zootaxa, 2020)
Nereis articulata Ehlers, 1887 is senior primary homonym to Nereis articulata Hsueh, 2020 from Taiwan. The older Nereis articulata name has been transferred to the genus Ceratonereis Kinberg, 1865 in the subgenus Composetia Hartmann-Schröder, 1985 by Hartmann-Schröder (1985), although this placement may be unreliable (Bakken & Wilson, 2005). Nevertheless its original name is an available name and its recombination is in use. Hsueh (2020) mistakenly treated N. articulata Ehlers, 1887 as an unavailable name and described a new Nereis, which possesses articulated tentacular cirri, as Nereis articulata Hsueh, 2020. Nereis articulata Ehlers, 1887 has precedence based on Article 23.4 of the International Code of Zoological Nomenclature (1999). Thus, Nereis taichungensis nom. nov. is named herein as a replacement name for Nereis articulata Hsueh, 2020, a junior primary homonym to N. articulata Ehlers, 1887, and thus permanently invalid (Article 57.2).